Carotenoid Production by Rhodosporidium paludigenum Using Cassava Starch Hydrolyzed by Bacillus subtilis as Substrate - Warjoto, Renna Eliana; Felianti, Felianti; Lay, Bibiana Widiyati (Indonesian Journal of Natural Pigments, 2020)
Carotenoids are natural pigments with colors ranging from yellow to red that are beneficial for food, cosmetics, and animal feed industries. These pigments can be found in fruits, vegetables, algae, and microorganisms. Among all microorganisms that have been known to produce carotenoids, Rhodosporidium paludigenum is still poorly investigated. Therefore, this study aimed to determine the potential of carotenoid production by R. paludigenum using cassava starch hydrolyzed by Bacillus subtilis as a substrate. The cassava starch for hydrolysis was divided into four concentrations, i.e., 2%, 4%, 6%, and 8% w/v. During the hydrolysis period, the amylase enzyme activity produced by B. subtilis was evaluated. The reducing sugar concentration was then examined to determine the optimum medium for carotenoid production. The highest amylase enzyme activity was produced on the second day in all cassava starch concentrations. However, the highest reducing sugar concentration was discovered in the 6% w/v cassava starch concentration. Thus, a batch submerged fermentation for carotenoid production by R. paludigenum was performed using the hydrolysate as the sole substrate. At the end of the fermentation, the total carotenoid was extracted, and the concentration was determined using spectrophotometry. The total yield of xanthophyll over biomass was higher than that of Î²-carotene. These findings elucidated the potency of cassava starch hydrolysate obtained from the starch hydrolyzed by B. subtilis, for carotenoid production by the red yeast R. paludigenum.